A study of smoking policies and regulations in Malaysia / Siti Nor Aishah Abdullah…[et al.] - Abdullah, Siti Nor Aishah; Maaruf, Mohammad Farhan; Kimin, Mohammad Azlan; Elias, Izuan (2009)
As any other country around the globe, Malaysia is not being left out with the smoking related issues. This research is conducted to examine the availability of any laws of no smoking hence evaluating the sufficiency of them. Then, the said laws shall be determined for its capability or should it be otherwise drafted or enacted. Data and information will be gathered from library, internet databases, interviews and questionnaires distribution. Findings will show whether or not the research objectives are established thus completing the research successfully. This research is mainly to see whose fault it is to be the cause of the smoking-related problems faced to date. For all that care, whosever fault shall be, there will be recommendation provided to curb with the problem hence providing better surroundings and environments for time to come. It is hoped that this research can open every eyes and lent every ears from every layers of community to take the gist of this research and use it to provide the best for future generations.